The ABCs of IP addressing - Held, Gilbert, 1943- (Auerbach Publications, 2002)
Our world is rapidly becoming an Internet-based world, with tens of millions of homes, millions of businesses, and within a short period of time, possibly hundreds of millions of mobile professionals accessing the literal mother of all networks. One of the key problems affecting many Internet users, ranging from individual professionals to networking managers and administrators, is a lack of knowledge concerning Internet Protocol (IP) addressing. A detailed reference guide, The ABCs of IP Addressing provides you with the detailed information about the key challenges of IP addressing and.